2018
DOI: 10.1016/j.exer.2018.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Reduced intraepithelial corneal nerve density and sensitivity accompany desiccating stress and aging in C57BL/6 mice

Abstract: Dry Eye disease causes discomfort and pain in millions of patients. Using a mouse acute desiccating stress (DS) model we show that DS induces a reduction in intraepithelial corneal nerve (ICN) density, corneal sensitivity, and apical extension of the intraepithelial nerve terminals (INTs) that branch from the subbasal nerves (SBNs). Topical application of 0.02% Mitomycin C (MMC) or vehicle alone has no impact on the overall loss of axon density due to acute DS. Chronic dry eye, which develops progressively as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
75
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 51 publications
(67 reference statements)
7
75
1
Order By: Relevance
“…In contrast, SBNP corneal nerve fibers are lost in mice, and do not change in Sprague Dawley (SD) rats. 17,31,33,34 The exact mechanism of the age-related increase in the density of the rat SBNP remains unknown, but it is likely that differences exist between species or strain regarding the maturity of corneal nerves. During corneal aging, several small-diameter subbasal nerves can arise from large-diameter subbasal nerves.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, SBNP corneal nerve fibers are lost in mice, and do not change in Sprague Dawley (SD) rats. 17,31,33,34 The exact mechanism of the age-related increase in the density of the rat SBNP remains unknown, but it is likely that differences exist between species or strain regarding the maturity of corneal nerves. During corneal aging, several small-diameter subbasal nerves can arise from large-diameter subbasal nerves.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 By contrast, several rodent studies have demonstrated agerelated changes to corneal structure, including an increase in the thickness of Descemet's membrane and a decrease in endothelial cell density. 10,11 The neural architecture has also shown significant changes including a reduction in density in both the SBNP [12][13][14] and SNTs. 14 Functionally, Stepp et al 13 demonstrated that mechanical corneal sensitivity in mice decreased with age, which paralleled a reduced density of sub-basal nerve axons, despite no change to SNTs.…”
mentioning
confidence: 99%
“…1 The density of sensory nerves is influenced by many factors, including sex, age, surgery, and the use of contact lenses. [3][4][5][6] Through the release of neuropeptides, this dense network of corneal nerves exerts different functions in both healthy and pathological conditions, including nerve/ epithelial layer homeostasis and production of tears. 3 A significant part of the corneal sensory nerves contain the neuropeptide Substance P (SP), 7,8 which exerts its activities by binding to the members of the G protein-coupled neurokinin receptors, expressed by a multitude of cell populations.…”
mentioning
confidence: 99%
“…[3][4][5][6] Through the release of neuropeptides, this dense network of corneal nerves exerts different functions in both healthy and pathological conditions, including nerve/ epithelial layer homeostasis and production of tears. 3 A significant part of the corneal sensory nerves contain the neuropeptide Substance P (SP), 7,8 which exerts its activities by binding to the members of the G protein-coupled neurokinin receptors, expressed by a multitude of cell populations. 9,10 Among neurokinin receptors, Neurokinin 1 receptor is expressed mainly on neuronal and immune cells, [11][12][13][14] and it has the highest affinity for SP.…”
mentioning
confidence: 99%
See 1 more Smart Citation